TÚRK XALÍQ ERTEKLERI HÁM ONÍŃ QARAQALPAQ FOLKLORÍNA BAYLANÍS MÁSELELERI - Sultanova, J. (SCIENCE and SOCIETY, 2023)
The article talks about Turkish folk tales and their connection with Karakalpak folklore. Similarities are comparatively studied between the heroes of Turkish and Karakalpak fairy tales. The typological genesis are also briefly discussed of Karakalpak folklore and literary-folklore connections.
Keywords: Turkish fairy tales; typological genesis; literary-folklore; relations; motive; literary relations